Market Reaction Toward the Detailed Content of Disclosure in the Modified Audit Opinion: Case of Indonesia - Wijaya, Hana; Herusetya, Antonius (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
This study examines the market reaction toward information content in the auditors' opinions measured by the number of paragraphs and detailed disclosures in additional and modified paragraphs in the modified audit opinion. The study sample was taken from all public companies on the Indonesian Stock Exchange, except for the financial industries in 2018-2020. Hypotheses tests were carried out using linear multiple regression models. With a total sample of 1017 firm-year observations for 339 listed companies, our study found evidence that the market reacted negatively to disclosures in audit opinions in the form of the number of paragraphs in the modified audit opinions. However, this study did not find evidence that the market reacts to the number of detailed contents in additional paragraphs and modification paragraphs. Our further tests found strong evidence of incremental information captured by the capital market players in the form of positive reactions to the number of paragraphs and detailed topics in the paragraphs of modified audit opinions during the Covid-19 pandemic in 2020. Results of the study provide practical implications that capital market players use detailed information contained in paragraphs of modified audit opinions to make investment decisions, reflected in the earnings response coefficient.